Outcomes of patients in nasopharyngeal adenoid cystic carcinoma in the IMRT era: a single-center experience - Wen-Bin Wu; Wu-Lin Cai; Ye-Hao Zou; Rui You; You-Ping Liu; Zhao-Di Yuan; Qiong Li; Wen-Chao Li; Zhi-Xuan Pi; Yu-Long Xie; Kai Wen; Ming-Yuan Chen; et al. (BMC Cancer, 2024)
Abstract Objective Nasopharyngeal adenoid cystic carcinoma (NACC) is a rare malignancy with special biological features. Controversies exist regarding the treatment approach and prognostic factors in the IMRT era. This study aimed to evaluate the long-term outcomes and management approaches in NACC. Methods Fifty patients with NACC at our institution between 2010 and 2020 were reviewed. Sixteen patients received primary radiotherapy (RT), and 34 patients underwent primary surgery. Results Between January 2010 and October 2020, a total of 50 patients with pathologically proven NACC were included in our analysis. The median follow-up time was 58.5 months (range: 6.0–151.0 months). The 5-year overall survival rate (OS) and progression-free survival rate (PFS) were 83.9% and 67.5%, respectively. The 5-year OS rates of patients whose primary treatment was surgery and RT were 90.0% and 67.3%, respectively (log-rank P = 0.028). The 5-year PFS rates of patients whose primary treatment was surgery or RT were 80.8% and 40.7%, respectively (log-rank P = 0.024). Multivariate analyses showed that nerve invasion and the pattern of primary treatment were independent factors associated with PFS. Conclusions Due to the relative insensitivity to radiation, primary surgery seemed to provide a better chance of disease control and improved survival in NACC. Meanwhile, postoperative radiotherapy should be performed for advanced stage or residual tumours. Cranial nerve invasion and treatment pattern might be important factors affecting the prognosis of patients with NACC.